In ovo testing of flavor and fragrance materials in Turkey Egg Genotoxicity Assay (TEGA), comparison of results to in vitro and in vivo data. (May 2018) - Kobets, Tetyana; Duan, Jian-Dong; Brunnemann, Klaus D.; Iatropoulos, Michael J.; Etter, Sylvain; Hickey, Christina; Smith, Benjamin; Williams, Gary M.
Abstract: Genotoxicity of flavor and fragrance materials was assessed in Turkey Egg Genotoxicity Assay (TEGA) using 32 P-nucleotide postlabeling (NPL) and comet assays to detect hepatic DNA adducts and strand breaks. Twenty materials having results in GADD45a-Gluc 'BlueScreen HC' genotoxicity assay, and standard in vitro and in vivo tests, were selected to evaluate the accuracy of TEGA. Quinoline (QUI) and 2-acetylaminofluorene (AAF) served as positive comparators. Two materials, p-tert-butyldihydrocinnamaldehyde (BDHCA) and methyl eugenol (MEU) produced DNA adducts. BDHCA, p-t-butyl-α-methylhydrocinnamic aldehyde (BMHCA), trans-2-hexenal (HEX) and maltol (MAL) produced DNA strand breaks. Fifteen other materials were negative in both assays. Based on reports of oxidative DNA damage induction by MAL and 4-hydroxy-2.5-dimethyl-3(2H) furanone (HDMF), modified comet assays were conducted. Positive comet findings for MAL were not confirmed, and only equivocal evidence of oxidative damage was found. Accordingly, MAL was judged to have equivocal genotoxicity in TEGA. HDMF was positive in modified comet assay, indicating an ability to produce oxidative DNA damage. TEGA showed modest concordance with results in regulatory in vitro assays. Findings in TEGA, with few exceptions, were concordant with the results of in vivo genotoxicity and carcinogenicity testing. Thus, TEGA is an attractive alternative model for the assessment of genotoxic potential of chemicals in vivo . Highlights: Out of 20 flavor and fragrance materials tested in TEGA, 5 were either positive or equivocal. In modified comet assay, 2 compounds produced evidence of oxidative damage. TEGA results showed modest concordance with those in regulatory in vitro assays. TEGA results were concordant with those of the genotoxicity and carcinogenicity testing of the chemical set in vivo. TEGA can be used as an alternative to the in vivo assays as a follow up for compounds that tested positive in vitro.